1997
DOI: 10.1530/eje.0.1360277
|View full text |Cite
|
Sign up to set email alerts
|

Decreased serum IGF-I and dehydroepiandrosterone sulphate may be risk factors for the development of reduced bone mass in postmenopausal women with endogenous subclinical hyperthyroidism

Abstract: Postmenopausal women with endogenous subclinical hyperthyroidism seem to have reduced bone mass, which does not correlate with serum thyroid hormone levels. Relative insufficiencies of IGF-I and dehydroepiandrosterone sulphate (DHEAS) might be additional risk factors for low bone density in these patients. We measured IGF-I, IGF-binding protein-3 (IGFBP-3) and DHEAS levels together with bone mineral density (BMD) of the femoral neck and lumbar spine in women with an autonomously functioning thyroid nodule. Six… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
2

Year Published

2001
2001
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 16 publications
1
11
2
Order By: Relevance
“…Changes in adrenocortical androgens in hyperthyroid patients, including elevated DHEAS levels and a low DHEA/DHEAS ratio, have previously been reported by Földes et al [13]. In contrast to these findings, DHEAS levels were normal in our patients, while the DHEA levels were significantly decreased.…”
Section: Discussioncontrasting
confidence: 52%
“…Changes in adrenocortical androgens in hyperthyroid patients, including elevated DHEAS levels and a low DHEA/DHEAS ratio, have previously been reported by Földes et al [13]. In contrast to these findings, DHEAS levels were normal in our patients, while the DHEA levels were significantly decreased.…”
Section: Discussioncontrasting
confidence: 52%
“…These include a relative deficiency of insulin-like growth factor type I, dehydroepiandrosterone sulfate [287], vitamin D receptor (VDR) polymorphisms [288] and estrogen [289]. The question as to whether prolonged hyperthyroidism due to L-T4 treatment increases the risk of fractures also remains controversial.…”
Section: Discussionmentioning
confidence: 99%
“…There are fewer data on the effect of sub-clinical hyperthyroidism on BMD in pre-menopausal women, although a few studies have shown no effect. 32,35,38 One study showed a decrease in BMD in femoral neck and phalanges but not lumbar spine. 33 The effect of sub-clinical hyperthyroidism on BMD in men has not been investigated adequately.…”
Section: Mechanisms Of Bone Loss In Hyperthyroidismmentioning
confidence: 99%